Implementing the ‘Integrated Model for Supervision’ for mental health and psychosocial support programming within humanitarian emergencies: A mixed-methods evaluation across six humanitarian contexts - Meg Ryan; Charles Zemp; Nadeen Abujaber; Marie Sonnenstuhl; Ahmad Alshibi; Pia Tingsted Blum; Ahlem Cheffi; Robert Fox; Sandra Githaiga; Hannah Green; Md. Saidul Islam; Salam Jabbour; et al. (Comprehensive Psychiatry)
Background: The ‘Integrated Model for Supervision’ (IMS) offers important guidance for how to provide supportive supervision within mental health and psychosocial support (MHPSS) programming in humanitarian emergencies. The current study sought to (i) describe how the IMS was implemented following IMS training; (ii) assess whether delivery of the IMS training is associated with changes in a selection of theoretically supported quantitative outcomes; and (iii) elicit feedback on the IMS and its implementation process. Methods: Data was collected from a participant pool of n = 119 individuals from six different humanitarian organisations that had previously participated in an IMS training. For the first and third objectives, interviews at 6- and 12-months post-training were conducted and thematically analysed. For the second objective, timepoint comparison analytical techniques were used across five distinct timepoints. Results: Quantitative findings showed significant increases in participant self-efficacy, supervision knowledge, and supervision confidence, alongside some evidence of reductions in participant burnout. Qualitatively, participants underscored the IMS's efficacy in creating supportive supervision structures within their organisations, identified barriers and facilitators to implementation and proposed strategies for sustainability. Additionally, they highlighted positive impacts of implementing the IMS on staff, organisational culture, and service quality. Discussion/conclusion: This study supports the effectiveness and acceptability of the IMS in enhancing the capacity of organisations to provide supportive supervision in humanitarian contexts, as key to promote the wellbeing of humanitarian MHPSS workers and the quality of the services they deliver. Challenges remain, however, to ensure sustainable implementation of the IMS, which guide ongoing efforts towards its improvement.